The antagonistic activity profile of naloxone in μ-opioid receptor agonist-induced psychological dependence. (14th September 2020) - Nakamura, Atsushi; Yasufuku, Kana; Shimada, Shinji; Aritomi, Hiroyuki; Furue, Youko; Chiba, Hiroki; Muramoto, Mami; Takase, Kenji; Koike, Katsumi; Matsumoto, Tomoko; Shimada, Tomoka; Watari, Ryosuke; et al.
Highlights: Naloxone shows competitive antagonistic activity against μ-opioid receptor agonists. Oxycodone:naloxone (1:0.5) does not produce conditioned place preference. An appropriate dose of naloxone can antagonize the psychological dependence on oxycodone. Abstract: Naloxone is a μ-opioid receptor antagonist that has been used to prevent overdose-related respiratory depression and deaths by the illicit use of opioids. Naloxone can also deter the abuse potential of opioids, but little has been reported regarding its antagonistic activity profile against opioid-induced psychological dependence. This study aimed to confirm the antagonistic activity profile of naloxone against several μ-opioid receptor agonists and investigate whether naloxone could affect the psychological dependence induced by widely used μ-opioid receptor agonist, oxycodone. In the Guanosine-5'-o-(3-thio) triphosphate (GTPγS) binding assay, naloxone (30−30, 000 nM) inhibited the GTPγS binding induced by oxycodone, hydrocodone, morphine, and fentanyl. It elicited parallel rightward shifts in the concentration-response curves, indicating that naloxone possessed a competitive antagonistic activity profile against these μ-opioid receptor agonists. In the conditioned place preference test, oxycodone (0.01−1 mg/kg, i.v.) produced dose-dependent increases in place preference. The increased place preference induced by oxycodone (1 mg/kg) was significantly attenuated by co-administration of naloxone at a dose of 0.5 mg/kg but not 0.01 mg/kg. Naloxone (0.5 mg/kg, i.v.) also blocked oxycodone (1 mg/kg)-induced dopamine release in nucleus accumbens; however, at a lower dose (0.01 mg/kg), it did not affect the intrinsic dopamine release by oxycodone. These results indicate that the psychological dependence of oxycodone could be antagonized by naloxone, depending on the dose. This characterization might lead to a better understanding of the competitive antagonistic activity profile of naloxone for μ-opioid receptor in the brain.